Managed Judicial Discretion: An Institutional Framework for Addressing Legal Uncertainty - Muhammad Ikram Nur Fuady; Syarif bin Muhammadromli Samae; Hendri K. (Gemini Littera Publishing, 2026)
This article examines the relationship between judicial discretion and legal uncertainty from a socio-legal and comparative perspective. While conventional legal theory often treats legal uncertainty as a deficiency of the legal system, this article argues that uncertainty is an inherent consequence of adjudication, arising from the open-textured nature of legal norms, legal pluralism, and institutional constraints. Employing a conceptual legal research design supported by comparative analysis of selected jurisdictions, the study explores how judicial discretion operates within different legal and institutional settings. The analysis demonstrates that legal uncertainty is not merely the product of normative ambiguity, but also emerges from the interaction between interpretative practices, institutional capacity, and competing sources of legal authority. To address this challenge, the article develops the concept of managed judicial discretion as a theoretical framework for balancing flexibility and legal certainty. This framework emphasizes the importance of interpretative guidelines, consistency in the use of precedent, transparency in judicial reasoning, and judicial oversight as institutional mechanisms for structuring judicial discretion. The article concludes that legal certainty is better understood as an institutional achievement rather than a product of rigid legal rules. Accordingly, effective judicial reform should focus not on eliminating discretion, but on improving its governance through accountable and coherent institutional arrangements.